Observer‐blind randomized controlled study of a cosmetic blend of safflower, olive and other plant oils in the improvement of scar and striae appearance. (12th December 2017) - Bielfeldt, S.; Blaak, J.; Staib, P.; Simon, I.; Wohlfart, R.; Manger, C.; Wilhelm, K. P.
Abstract: Objective: The normal process of skin tissue repair following injury invariably results in visual scarring. It is known that topical treatment with hydrophobic cosmetics rich in silicone and mineral oil content can improve the appearance of scars and striae. Given lifestyle preferences of many cosmetic consumers towards so‐called natural treatments, the objective of this controlled randomized study was to investigate the efficacy of a plant body oil rich in oleic and linoleic acids (Bio Skin Oil ® ) for improving the appearance of scars and striae. Methods: A panel of 80 volunteers with non‐hypertrophic scars (40) or stretch marks (40) not older than 3 years applied a cosmetic face and body oil for 8 weeks. Compared to an untreated scar/stretch mark region, a blinded investigator as well as volunteer assessments with given observed parameters demonstrated the efficacy of the oil under test. Results: On the Observer Scar Assessment Scale (OSAS), the mean score was reduced on the product‐treated area by approximately 5% ( P = 0.006). The untreated area remained unchanged. Observed effects by volunteers were more pronounced – Patient Scar Assessment Scale (PSAS) giving a reduction of approximately 20% on the treated area, and on the control untreated area a reduction of approximately 6%. The overall product effect of 14% was shown to be clearly significant ( P = 0.001). All statements relating to product traits achieved higher frequencies of agreements than of non‐agreements and were therefore assessed positively by the volunteers. Highest frequencies of agreements occurred in statements that the test product provides a long‐lasting, soft and supple skin feeling (93%); caring effect (87%); and quick absorbance (84%). Agreement was also found for statements that the product improves the skin appearance (61%) and that scars/striae appear less pronounced (51%). Only 17% of volunteers felt the oil had no benefit to the appearance of their scars/striae. Conclusions: The oil blend under test is effective in improving the appearance of non‐keloid scars and striae. Further work is required to understand the mechanisms of how plant oil fatty acids ameliorate scar and striae appearance.